Advances in discourse analysis of translation and interpreting : linking linguistic approaches with socio-cultural interpretation - Wang, Binhua (Professor of translation); Munday, Jeremy (London ; New York : Routledge, 2020)
"This edited thematic collection features latest developments of discourse analysis in translation and interpreting studies. It investigates the process of how cultural and ideological intervention is conducted in translation and interpreting using a wide array of discourse analysis and systemic functional linguistic approaches and drawing on empirical data from the Chinese context. The book is divided into four main sections: 1) uncovering positioning and ideology in interpreting and translation, 2) linking linguistic approach with socio-cultural interpretation, 3) discourse analysis into news translation, and 4) analysis of multimodal and intersemiotic discourse in translation. The different approaches to discourse analysis provide a much-needed contribution to the field of translation and interpreting studies. This combination of discourse analysis and corpus analysis demonstrates the interconnectedness of this fields and offers a rich source of conceptual and methodological tools. This book will appeal to scholars and research students in translation and interpreting studies, cross-linguistic discourse analysis and Chinese studies"--
Introduction Binhua Wang and Jeremy Munday 1. Presentation, re-presentation and perception of China's political concepts -- A corpus-based analysis into the discourse on the 'Belt and Road' (Binhua Wang) 2. From linguistic manipulation to discourse re-construction: a case study of conference interpreting at the World Economic Forum in China (Fei Gao) 3. A corpus-based CDA on government interpreters' metadiscursive (re)construction of truth, fact and reality (Chonglong Gu) 4. Competing narratives and interpreters' choices: a case study on a China-US military exercise (Qianhua Ouyang and Qiliang Xu) 5. Functions of the pronoun 'we' in the English translations of Chinese government reports (Hailing Yu and Canzhong Wu) 6. Interpreting as institutional gatekeeping: a critical discourse analysis of interpreted questions at the Chinese Foreign Minister's press conferences (Xin Li and Ranran Zhang) 7. Stance mediation in media translation of political speeches: an analytical model of appraisal and framing in news discourse (Li Pan & Chuxin Huang) 8. Representations of the 2014 Hong Kong protests in news translation: a corpus-based critical discourse analysis (Yuan Ping) 9. Reframing China in conflicts: a case study of English translation of South China Sea dispute (Binjian Qin) 10. Translation of public notices in Macao: a multimodal perspective (Xi Chen) 11. Representation of identity in dubbed Italian versions of multicultural sitcoms: An SFL perspective (Marina Manfredi)
OCLC-licensed vendor bibliographic record.
Keywords: Translating and interpreting -- Political aspects -- China; Translating and interpreting -- Social aspects -- China; Discourse analysis -- China; LANGUAGE ARTS & DISCIPLINES / Linguistics